2014
DOI: 10.1016/j.humov.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment to a real time fractal visual stimulus modulates fractal gait dynamics

Abstract: Fractal patterns characterize healthy biological systems and are considered to reflect the ability of the system to adapt to varying environmental conditions. Previous research has shown that fractal patterns in gait are altered following natural aging or disease, and this has potential negative consequences for gait adaptability that can lead to increased risk of injury. However, the flexibility of a healthy neurological system to exhibit different fractal patterns in gait has yet to be explored, and this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 55 publications
12
51
1
Order By: Relevance
“…Accordingly, optimal structures of frequency variability in participants and/or stimulus movements might also facilitate spontaneous visuomotor synchronization. Future research may well benefit from controlling the variability structure in participants' movement and employing both correlated and uncorrelated noise structures for stimulus movements (Hunt, McGrath, & Stergiou, 2014;Rhea, Kiefer, D'Andrea, Warren, & Aaron, 2014;Torre, Varlet, & Marmelat, 2013). The facilitating effects of external stimulus noise may be strengthened with more correlated structures.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, optimal structures of frequency variability in participants and/or stimulus movements might also facilitate spontaneous visuomotor synchronization. Future research may well benefit from controlling the variability structure in participants' movement and employing both correlated and uncorrelated noise structures for stimulus movements (Hunt, McGrath, & Stergiou, 2014;Rhea, Kiefer, D'Andrea, Warren, & Aaron, 2014;Torre, Varlet, & Marmelat, 2013). The facilitating effects of external stimulus noise may be strengthened with more correlated structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the next 15 minutes (synchronization phase), the participants synchronized their gait cycle to a visual metronome that exhibited persistence (DFA α = 0.98). As in our previous work [27], the visual metronome consisted of a red flashing square that was projected in front of the treadmill and participants were asked to synchronize to the metronome by being at right heel contact when the red square flashed. The average interval between red square flashes was 1.00±0.07 sec.…”
Section: Methodsmentioning
confidence: 99%
“…This experiment was designed to replicate and expand our previous work using a visual stimulus exhibiting fractal timing patterns as a mechanism for individuals to develop a desired change in fractal timing patterns of gait [27]. This was accomplished by instructing the participants to entrain their gait cycle to the visual stimulus.…”
Section: Experiments 1 – Determining Whether Fractal Gait Patterns Arementioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that the auditory stimuli have the strongest influence on human gait compared to other types of stimuli [4]. See also [5]. In another work Kaipust et al investigated the effects of different auditory stimuli on two groups of subjects, young and elderly adults.…”
Section: Introductionmentioning
confidence: 99%